Course in General Linguistics - Ferdinand de Saussure, editor: Perry Meisel, Haun Saussy (Columbia University Press, 2011)
â€œSignifi erâ€ and â€œSignifi edâ€: Reclaiming Saussureâ€™s Legacy This new edition of Saussureâ€™s Course in General Linguistics (1916) restores the Saussure that generations of English readers grew up on: Wade Baskinâ€™s 1959 translation. In addition to its inherent elegance, Baskinâ€™s translation of the lectures Saussure gave at the end of his life at the University of Geneva is indispensable for a very particular reason, one that Roy Harrisâ€™s 1983 translation wholly obscures: the rendition of Saussureâ€™s terms â€œ signifi ant â€ and â€œ signifi Ã© â€ ( CLG 1972, 99) as â€œsignifi erâ€ and â€œsignifi edâ€ ( CGL 1959, 67). These equivalent neologisms in French and English embody precisely what is revolutionary about Saussureâ€™s thought and what is specifi c to it. Baskinâ€™s translation makes this revolution clear. Saussure presents the solution to a problem in the history of ideas that stretches back to Plato and that reached crisis proportions in the late nineteenth century: the problem of reference. Most familiar as a problem in poetics, it is a problem in all media, including the life sciences, which is why Saussure reconceived the problem of reference as one of signifi cation. Many false starts delayed Saussureâ€™s discovery until the end of his life, daunted as he was by the numerous historical contexts in which he had to test his ideas in order to ensure their durability. Traditionally cast as the problem of mimesisâ€”of language as imitating or representing what it refers toâ€”the problem of reference is put on an entirely different footing by what Saussure eventually achieved.